Preparation method and application of additive for positive electrode and negative electrode of lead-carbon battery
By adding acidic oxygen-containing functional groups modified carbon materials to the positive and negative electrodes of lead-carbon batteries, the problems of short cycle life and low energy density of traditional lead-carbon batteries are solved, and the cycle stability and high-rate charging performance of lead-carbon batteries are significantly improved.
Patent Information
- Application Number
- CN202510362327.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
During the charging and discharging cycle, traditional lead-acid batteries have problems such as short cycle life, serious sulfateization of active substances and low energy density, and lead-carbon batteries have limited self-discharge and mass transfer capabilities of the negative electrode at hydrogen evolution and positive electrode.
By adding acidic oxygen-containing functional groups modified carbon material to the positive and negative electrodes of lead-carbon batteries as additives, side reactions are reduced, moisture in the electrolyte is reduced, and cycle stability and cycling performance in high-rate charge state are improved.
It significantly improves the discharge capacity and cycle life of the battery, enhances the stability of the electrode, improves the capacitance characteristics, suppresses the sulfation phenomenon, and improves the overall performance of the battery.
Smart Images

Figure CN119873800A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lead-carbon batteries, and more specifically, to a preparation method and application of positive and negative electrode additives for lead-carbon batteries. Background Art
[0002] With the rapid development of human economy, the demand for energy and power is growing. Lead-acid batteries are widely used in electric vehicles, emergency power supplies, and renewable energy storage due to their mature technology, low cost, and good recyclability. However, traditional lead-acid batteries have many shortcomings in the charge and discharge cycle. (1) Short cycle life: The number of cycles of traditional lead-acid batteries is generally between 300 and 600 times. As the charge and discharge proceed, the electrode material will gradually age, reducing the performance of the battery. (2) Severe sulfation of active substances: During deep discharge and long-term static storage, lead sulfate crystals will form and aggregate inside the lead-acid battery, making it difficult for the battery to be fully converted into positive and negative active substances during charging, resulting in reduced capacity and inability to fully recover. (3) Low energy density: The energy density of lead-acid batteries is relatively low, and the energy stored is limited under the same volume and weight.
[0003] However, lead-carbon batteries have significantly improved the above problems by adding carbon materials to the negative electrode of lead-acid batteries. The use of carbon materials not only enhances the charge and discharge performance and cycle life of the battery, but also alleviates the sulfation phenomenon to a certain extent, and improves the energy density and power density of the battery, making it show great development potential in the field of new energy storage. However, lead-carbon batteries still face some challenges, such as the self-discharge problem of hydrogen evolution at the negative electrode, and the overall rate performance and cycle performance of the battery are limited by the positive electrode. Therefore, how to reduce the hydrogen evolution phenomenon of the carbon-containing negative electrode and improve the mass transfer capacity in the thicker positive electrode active material to further improve the overall performance of the battery has become an urgent problem to be solved in the current lead-acid battery field. In particular, the development of a low-cost, simple to operate and easy to industrialize additive is of great significance for the promotion and application of lead-acid batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a preparation method and application of positive and negative electrode additives for lead-carbon batteries. The present invention reduces the side reactions of the positive and negative electrodes and reduces the reduction of water in the electrolyte, thereby improving the cycle stability of the lead-carbon battery and the cycle performance of the high-rate state of charge.
[0005] To achieve the above object, the technical solution of the present invention is as follows: A preparation method for positive and negative electrode additives for lead-carbon batteries comprises: mixing Ketjen black with acid and dispersing them uniformly, then shunting the obtained mixture at 70-90°C for 8-24h, washing and centrifuging after cooling until the pH value is neutral, and then vacuum drying and grinding to obtain the positive and negative electrode additives for lead-carbon batteries.
[0006] Optionally, the acid is concentrated nitric acid with a concentration of 40%.
[0007] Optionally, the mass ratio of the Ketjen black to the concentrated nitric acid is 1:50-70.
[0008] Optionally, the particle size of the Ketjen black is 20-50 nm.
[0009] Optionally, the particle size of the additive is 25~50nm.
[0010] The invention also discloses an application of the positive and negative electrode additives for lead-carbon batteries prepared by the above-mentioned preparation method in lead-carbon batteries.
[0011] Optionally, the application includes: preparing positive electrode lead paste of a lead-carbon battery and negative electrode lead paste of a lead-carbon battery; preparing positive plates and negative plates; The positive electrode plate and the negative electrode plate are respectively immersed in a sulfuric acid solution for reaction; After the soaking is completed, the electrode plates are cured to obtain the positive electrode plates and negative electrode plates soaked in acid; The acid-soaked positive and negative plates are assembled into a battery. The separator is made of one of the AGM and PE separator materials. The electrolyte is made of a density of 1.4 g / cm 3 Sulfuric acid solution.
[0012] Optionally, the positive electrode lead paste of the lead-carbon battery is prepared by adding 0.2% by weight of lead powder as an additive for positive and negative electrodes of lead-carbon batteries.
[0013] Optionally, the preparation method of the positive electrode plate includes: dry mixing the positive and negative electrode additives for lead-carbon batteries, lead powder, red lead, short fibers and carbon fibers in a paste mixer for 5 to 10 minutes to obtain a dry mixture; adding deionized water to the dry mixture and stirring for 10 to 20 minutes to obtain a wet mixture, and maintaining the lead paste temperature ≤ 60°C; slowly adding sulfuric acid in small amounts to the wet mixture and stirring for 10 to 20 minutes to produce a paste to obtain a positive electrode lead paste for a lead-carbon battery, and applying it to obtain the positive electrode plate.
[0014] Optionally, the negative electrode lead paste of the lead-carbon battery is prepared by adding 0.5% by weight of lead powder as an additive for positive and negative electrodes of lead-carbon batteries.
[0015] Optionally, the preparation method of the negative electrode plate includes: dry mixing the positive and negative electrode additives for lead-carbon batteries, lead powder, barium sulfate, short fibers, sodium lignin sulfonate and acetylene black in a paste mixer for 5 to 10 minutes to obtain a dry mixture; adding deionized water to the dry mixture and stirring for 10 to 20 minutes to obtain a wet mixture, and keeping the lead paste temperature ≤ 60°C; slowly adding sulfuric acid in small amounts to the wet mixture and stirring for 10 to 20 minutes to produce a paste to obtain a negative electrode lead paste for a lead-carbon battery, and applying it to obtain the negative electrode plate.
[0016] Implementing the embodiments of the present invention will have the following beneficial effects: The present invention significantly improves the discharge capacity and cycle life of the battery by adding Ketjen black rich in acidic oxygen-containing functional groups to the positive and negative lead pastes of the lead-carbon battery. Ketjen black itself has a unique hollow spherical morphology, high specific surface area and ultra-high conductivity, and also has a special branched structure. After being treated with concentrated nitric acid, although the surface structure of Ketjen black does not change significantly, the degree of graphitization defects increases, which introduces more acidic oxygen-containing functional groups to its surface, further improving its performance. Specifically, the beneficial effects of the present invention are reflected in the following aspects: 1. Enhanced electrode stability: The increase of acidic oxygen-containing functional groups effectively inhibits the side reactions of the electrodes in the battery, enhances the stability of the active material skeleton, improves the problem of active material shedding, and reduces water loss. These improvements significantly improve the cycle life of the battery.
[0017] 2. Improve capacitance characteristics and inhibit sulfation: Ketjen black modified with acidic oxygen-containing functional groups as a capacitor carbon material gives the battery better capacitance characteristics, improves the mass transfer efficiency of active substances, and effectively inhibits the sulfation phenomenon of the negative electrode, thereby further improving the performance of the battery.
[0018] 3. Improved dispersibility and contact performance: The carbon material modified with acidic oxygen-containing functional groups has good dispersibility in the solution and will not settle. As an additive, it can promote the close contact between lead powder and carbon material, while ensuring the full contact between electrolyte and active substances, thereby significantly improving the electrochemical performance of the battery plate and playing a positive role in promoting the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a flow chart for preparing the positive lead-carbon battery.
[0020] Figure 2 The present invention is a flow chart for preparing the negative lead-carbon battery.
[0021] Figure 3 The electrochemical performance diagrams of Example 1, Example 3 and Comparative Example 1 of the present invention are shown.
[0022] Figure 4 The electrochemical performance diagrams of Example 2, Example 4 and Comparative Example 2 of the present invention are shown.
[0023] Figure 5 These are the different current density cycle performance diagrams of Example 1, Example 3 and Comparative Example 1 of the present invention.
[0024] Figure 6 These are the different current density cycle performance diagrams of Example 2, Example 4 and Comparative Example 2 of the present invention.
[0025] Figure 7 It is a rate performance diagram of Example 1, Example 3 and Comparative Example 1 of the present invention.
[0026] Figure 8 It is a rate performance diagram of Example 2, Example 4 and Comparative Example 2 of the present invention.
[0027] Fig. 9 It is a cycle test diagram of Example 1, Example 3 and Comparative Example 1 of the present invention.
[0028] Fig.10 Graphs showing the coulombic efficiencies of Example 1, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0030] Example 1 1. Preparation of positive plate Lead powder (100 parts), red lead (2 parts), short fiber (0.15 parts), carbon fiber (0.2 parts) are dry mixed in a paste machine for 5-10 minutes to obtain a dry mixture; add an appropriate amount of deionized water and stir for 10-20 minutes to obtain a wet mixture, and keep the lead paste temperature below 60°C; add sulfuric acid to the wet mixture in small amounts and multiple times, stir evenly, and stir for 10-20 minutes to produce a paste to obtain a positive electrode lead paste for a lead-carbon battery, which is then applied to obtain a positive electrode plate. After the obtained plate is soaked in a sulfuric acid solution for reaction, it is cured in a constant temperature and humidity chamber using a positive electrode plate curing process to obtain the obtained plate.
[0031] 2. Preparation of negative plate Lead powder (100 parts), barium sulfate (0.83 parts), short fibers (0.15 parts), sodium lignin sulfonate (0.2 parts), and acetylene black (0.2 parts) are dry mixed in a paste machine for 5 to 10 minutes to obtain a dry mixture; an appropriate amount of deionized water is added and stirred for 10 to 20 minutes to obtain a wet mixture, and the temperature of the lead paste is kept below 60°C; sulfuric acid is slowly added to the wet mixture in small amounts and multiple times, stirred evenly, and the stirring time is 10 to 20 minutes, and the paste is obtained to obtain a negative electrode lead paste for a lead-carbon battery, which is then applied to obtain a negative electrode plate. The obtained electrode plate is soaked in a sulfuric acid solution for reaction, and then cured in a constant temperature and humidity chamber using a negative electrode plate curing process to obtain the obtained electrode plate.
[0032] 3. Assemble the battery The positive plate and the negative plate are assembled into a battery in a "two-in-one" manner (two negative plates plus one positive plate), the separator is AGM, and the electrolyte is a 1.4g / cm 3 Sulfuric acid solution; after sealing, the monomer product is made according to the normal production process of lead-acid battery. A 2V·5Ah lead-carbon battery is obtained. It is recorded as a positive electrode blank battery and numbered 1#.
[0033] Example 2 The difference between this embodiment and embodiment 1 is that the lead-carbon battery is assembled differently, specifically as follows: in step 3, the negative plate and the positive plate are assembled into a battery in a "two-in-one" manner (two positive plates plus one negative plate), which is recorded as a negative blank battery and numbered 2#.
[0034] Example 3 The difference between this embodiment and embodiment 1 is that a carbon material rich in acidic oxygen-containing functional groups is added to the positive electrode lead paste of the lead-carbon battery in this embodiment as a positive electrode additive, specifically: Before mixing with the paste, a carbon material rich in acidic oxygen-containing functional groups was prepared. The preparation method was as follows: 0.2 parts of Ketjen black (particle size of 20-50 nm) was weighed and ultrasonicated in 12 parts of 40% concentrated nitric acid for 30 minutes, and then the mixture was split at 85°C for 12 hours. After cooling, the carbon material was repeatedly washed with ultrapure water and centrifuged until the pH value was neutral. After vacuum drying and grinding, a carbon material rich in acidic oxygen-containing functional groups with a particle size of 25-50 nm was obtained as a positive electrode additive.
[0035] Weigh 0.2% of the mass of lead powder of a carbon material rich in acidic oxygen-containing functional groups, mix it with lead powder, red lead, short fibers and carbon fibers, and prepare a positive electrode plate according to the treatment method of Example 1. The prepared positive electrode lead-carbon battery modified with acidic oxygen-containing functional groups is numbered 1-2#.
[0036] Example 4 The difference between this embodiment and embodiment 2 is that: the lead paste of the lead-carbon battery negative electrode in this embodiment further adds a carbon material modified with acidic oxygen-containing functional groups as a negative electrode additive, specifically: Before mixing with the paste, a carbon material rich in acidic oxygen-containing functional groups was prepared. The preparation method was as follows: 0.5 parts of Ketjen black (particle size of 20-50 nm) was weighed and ultrasonicated in 30 parts of 40% concentrated nitric acid for 30 minutes, and then the mixture was split at 85°C for 12 hours. After cooling, the carbon material was repeatedly washed with ultrapure water and centrifuged until the pH value was neutral. After vacuum drying and grinding, a carbon material rich in acidic oxygen-containing functional groups with a particle size of 25-50 nm was obtained as a negative electrode additive.
[0037] Weigh 0.5% of the mass of lead powder of a carbon material rich in acidic oxygen-containing functional groups, mix it with lead powder, barium sulfate, short fibers, sodium lignin sulfonate, and acetylene black, and prepare a negative electrode plate according to the treatment method of Example 2. The prepared negative electrode lead-carbon battery modified with acidic oxygen-containing functional groups is numbered 2-2#.
[0038] Comparative Example 1 The only difference between this comparative example and Example 3 is that only 0.2 parts of Ketjen black without acidic functional group modification is added as a positive electrode additive to the positive electrode plate of this comparative example, and the positive electrode plate is prepared according to the treatment method of Example 3, and the prepared positive lead-carbon battery is numbered 1-1#.
[0039] Comparative Example 2 The only difference between this comparative example and Example 4 is that only 0.2 parts of Ketjen black without acidic functional modification is added as a negative electrode additive to the negative electrode plate of this comparative example, and the negative electrode plate is prepared according to the treatment method of Example 4, and the prepared negative electrode lead-carbon battery is numbered 2-1#.
[0040] Embodiment 5-8 Compared with Example 3, the difference between this embodiment is that the mass ratio of Ketjen black to concentrated nitric acid is changed. Except for the above difference, other operations are the same and will not be repeated here. The specific mass ratios of Ketjen black to concentrated nitric acid are 1:40, 1:50, 1:70, and 1:80, respectively. They are numbered 1-3#, 1-4#, 1-5#, and 1-6#, respectively.
[0041] Examples 9-12 Compared with Example 4, the difference between this embodiment is that the mass ratio of Ketjen black to concentrated nitric acid is changed. Except for the above difference, other operations are the same and will not be repeated here. The specific mass ratios of Ketjen black to concentrated nitric acid are 1:40, 1:50, 1:70, and 1:80, respectively. They are numbered 2-3#, 2-4#, 2-5#, and 2-6#, respectively.
[0042] Test Case Electrochemical tests were performed on the plates of the lead-carbon batteries with different positive electrode additives in Example 1, Example 3 and Comparative Example 1 of the present invention; and Example 2, Example 4 and Comparative Example 2, that is, the lead-carbon batteries with different negative electrode additives after formation to obtain the polarization current. The results are shown in Figure 3 , 4 As shown, it can be seen that for the lead-carbon battery with the addition of oxidized Ketjen black material, the side reactions of the electrodes are reduced to a certain extent, whether it is the positive electrode or the negative electrode, indicating that the acidic functional group-modified carbon slows down the side reactions and inhibits the sulfation of the electrode to a certain extent.
[0043] Comparison of the cycling performance of batteries with different positive electrode additives at different current densities of 0.1C, 0.2C, 0.5C and 0.1C and the initial discharge capacity at 0.1C current. Among them, the initial discharge capacity of batteries 1#, 1-1# and 1-2# are 84.49mAh / g, 89.37mAh / g and 95.39mAh / g, respectively. Figure 5 As shown in the figure, compared with the blank battery, the battery containing the carbon material modified with acidic oxygen-containing functional groups as the positive electrode additive is about 112.9% higher than the blank battery. The initial capacities of 2#, 2-1# and 2-2# batteries are 112.85mAh / g, 123.32mAh / g and 128.49mAh / g, respectively. Figure 6 As shown, the battery containing oxidized Ketjen black is about 113.8% higher than the blank negative electrode battery. At different current densities, the discharge capacity of 1-2# is the largest. The reason is that the acidic oxygen-containing functional group additive of the present invention improves the positive electrode rate performance of the battery, and the battery as a whole has a better ability to share large current discharge and a stronger ability to alleviate the rapid drop in voltage.
[0044] Similarly, the rate performance of batteries with different negative electrode additives 2#, 2-1# and 2-2# is as follows Figure 7 , 8 As shown. The simulated battery discharge capacity of the additive is higher than that of the blank battery at both high and low rates. Since there are a large number of acidic oxygen-containing functional groups on the carbon surface, on the one hand, the presence of the modified carbon provides new reaction active centers for the reduction reaction of the positive plate; on the other hand, the oxygen-containing functional groups on the carbon surface have a strong affinity with the electrolyte solution, allowing the two to fully contact, shorten the charge transfer resistance, reduce the internal resistance, and enhance the proton transfer rate.
[0045] Comparison of coulombic efficiency of batteries with different electrode additives at 0.5C 100% DOD deep discharge cycle test Fig. 9 , 10As shown. Under deep cycling, the discharge capacity of the simulated battery containing the carbon modified with acidic functional groups is much higher than that of the other two groups; its coulombic efficiency remains above 96%, and the extended cycle life shows that the carbon modified with acidic functional groups is quite reliable as an additive for lead-carbon batteries.
[0046] The initial discharge performance of lead-carbon batteries with different positive electrode additives prepared by different mass ratios of Ketjen black to concentrated nitric acid in Examples 3 and 5-8 of the present invention, and lead-carbon batteries with different negative electrode additives prepared by different mass ratios of Ketjen black to concentrated nitric acid in Examples 4 and 9-12 of the present invention are compared. The results are shown in Table 1-2.
[0047]
[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing positive and negative electrode additives for lead-carbon batteries, characterized in that: include: The Ketjen black and the acid are mixed and dispersed uniformly, and then the obtained mixture is split at 70-90° C. for 8-24 hours, cooled, washed and centrifuged until the pH value is neutral, and then vacuum dried and ground to obtain the positive and negative electrode additives for lead-carbon batteries.
2. The method for preparing positive and negative electrode additives for lead-carbon batteries according to claim 1, characterized in that: The acid is concentrated nitric acid with a concentration of 40%.
3. The method for preparing positive and negative electrode additives for lead-carbon batteries according to claim 2, characterized in that: The mass ratio of the Ketjen black to the concentrated nitric acid is 1:50-70.
4. The method for preparing positive and negative electrode additives for lead-carbon batteries according to claim 1, characterized in that: The particle size of the Ketjen black is 20-50 nm; The particle size of the additive is 25-50 nm.
5. Use of the positive and negative electrode additives for lead-carbon batteries prepared by the preparation method as described in any one of claims 1 to 4 in lead-carbon batteries.
6. The use according to claim 5, characterized in that: The application includes: preparing positive lead paste of lead-carbon battery and negative lead paste of lead-carbon battery; preparing positive plates and negative plates; The positive electrode plate and the negative electrode plate are respectively immersed in a sulfuric acid solution for reaction; After the soaking is completed, the electrode plates are cured to obtain the positive electrode plates and negative electrode plates soaked in acid; The acid-soaked positive and negative plates are assembled into a battery. The separator is made of one of the AGM and PE separator materials. The electrolyte is made of a density of 1.4 g / cm 3 Sulfuric acid solution.
7. The use according to claim 6, characterized in that: The positive electrode lead paste of the lead-carbon battery adopts a positive and negative electrode additive for lead-carbon batteries with 0.2% lead powder added by weight.
8. The use according to claim 7, characterized in that: The preparation method of the positive electrode plate comprises: dry mixing the positive and negative electrode additives for lead-carbon batteries, lead powder, red lead, short fibers and carbon fibers in a paste mixer for 5 to 10 minutes to obtain a dry mixed material; Add deionized water to the dry mixture and stir for 10 to 20 minutes to obtain a wet mixture, and keep the lead paste temperature ≤ 60° C.; Sulfuric acid is slowly added to the wet mixture in small amounts for multiple times and stirred for 10 to 20 minutes to obtain a paste, thereby obtaining a positive electrode lead paste for a lead-carbon battery, which is then applied to obtain the positive electrode plate.
9. The use according to claim 6, characterized in that: The negative electrode lead paste of the lead-carbon battery adopts a positive and negative electrode additive for lead-carbon batteries with 0.5% lead powder added by weight.
10. The use according to claim 9, characterized in that: The preparation method of the negative electrode plate comprises: dry mixing the positive and negative electrode additives for lead-carbon batteries, lead powder, barium sulfate, short fibers, sodium lignin sulfonate and acetylene black in a paste mixer for 5 to 10 minutes to obtain a dry mixed material; Add deionized water to the dry mixture and stir for 10 to 20 minutes to obtain a wet mixture, and keep the lead paste temperature ≤ 60° C.; Sulfuric acid is slowly added to the wet mixture in small amounts for multiple times and stirred for 10 to 20 minutes to obtain a paste, thereby obtaining a negative electrode lead paste for a lead-carbon battery, which is then applied to obtain the negative electrode plate.
Citation Information
Patent Citations
Activated carbon paste and method for manufacturing pole plate by activated carbon paste
CN102945959A
Lead paste for negative electrode of lead-carbon battery, preparation method of lead paste, polar plate for negative electrode of lead-carbon battery, and lead-carbon battery
CN108493448A
EFB start-stop battery positive and negative electrode with high charging acceptance capacity and preparation method thereof
CN109037597A
Preparation method of positive electrode conductive agent and conductive agent slurry of lithium ion battery
CN109777159A
Long-life lead-carbon battery and preparation method thereof
CN117613415A
Cited By
Method for preparing positive pole piece of lead-carbon battery by dry method, positive pole piece and battery
CN120545317A